On the Determination of Emission Standards for Air Pollutants Released from Stationary Gas Turbines - Zhitan LIU; Xi SHU; Aiyong YANG; Yugang LI (Zhongguo dianli, 2020)
As the environmental protection requirements become more stringent and installed capacity of stationary gas turbines keeps growing, the impacts of NOx emissions have been receiving increasingly more attention. However, the current national standard of "Emission Standards for Air Pollutants of Thermal Power Plants" does not provide sufficient guidelines because its emission limit settings are not well defined for particulate matter and SO2. This paper firstly compares and analyzes the pollutant sources, current status of the standards, emission status and monitoring methods of conventional air pollutants in terms of NOx, SO2 and particulate matter. Then, in the aspects of the technical feasibility, the advantages and usability of the standard, as well as the economic and environmental benefits in the transformation of stationary gas turbines carried out in Jiangsu Province, it is recommended that the NOx limit should be set to 15 mg/m3, and the emission limit of SO2 and particulate matter should be abolished.